Formulation of Anti-Acne Gel of Moringa oleifera L Ethanolic Extract and Antibacterial Test on Staphylococcus epidermidis - Dian Eka Ermawati; Cahyarani Intan Ramadhani (Institute for Halal Industry and System (IHIS) Universitas Gadjah Mada, 2019)
Moringa oleifera L. leaves contain flavonoid, alkaloid, and phenolic compounds which haveantibacterial activity. Staphylococcus epidermidis is one of the bacteria that causes acne. The purpose of this studyis to compare bacteriostatic ability of the extracts and gel for S. epidermidis bacteria and to get gel formula thatcan fulfills the physical properties of a good gel. Moringa leaves were extracted with maceration method usingethanol 70% in three days. HPMC 4000 was used as the polymer. Extract was added with variationconcentrations of 5, 10, and 15%. Physical evaluation of gel was organoleptic, homogeneity, pH, viscosity,adhesion, and spread tests for 4 weeks. In vitro bacteriostatic activity test with 1% clindamycin gel as positivecontrol and polymer gel as negative control. The result showed that variations concentrations of ethanolicextract of Moringa leaves affected the physical properties of gel including viscosity, pH, adhesion andspreadability. Bacteriostatic activity test of ethanolic extract of Moringa leaf was classified as strong activity,while 15% Moringa leaf ethanol extract gel was classified as moderate activity with average diameter was 9.14mm.